Effect of maternal anemia on cord blood haemoglobin of newborn - Rathoria, Richa; Rathoria, Ekansh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Anemia during pregnancy is linked to major maternal and fetal problems. The aim of the study was to find any correlation between maternal anemia and neonatal cord blood haemoglobin (Hb) levels. Methods: This cross-sectional study was done in the department of pediatrics and department of obstetrics and gynaecology at the Hind Institute of Medical Sciences, Barabanki over 9 months from January 2021 to September 2021. A total of 308 pregnant females more than 34 weeks of gestation who delivered participated in the study and cord blood hemoglobin of their new-born was collected. The mean maternal hemoglobin and mean cord blood hemoglobin were compared using the Pearson correlation coefficient in different groups i.e., non-anemic, anemic, mild, moderate, and severe anemic groups. Results: Out of 308 pregnant women, 198 (64.3%) were anemic, and 110 (35.7%) were nonanemic. The mean maternal hemoglobin among non-anemic mothers and anemic mothers was 11.91 (0.70) and 9.14 (1.56) respectively. The Pearson correlation coefficient of non-anemic, anemic, mild, moderate, and severe anemic groups were 0.6985, 0.8453, 0.7772, 0.6321, and 0.7226 respectively with a statistically significant p value<0.05 showing a positive correlation between maternal hemoglobin and cord hemoglobin. Conclusions: From this study, we concluded that maternal anemia affects neonatal cord blood hemoglobin. According to the findings, anemic women deliver new-born with lower hemoglobin levels than non-anemic mothers. The findings revealed a linear correlation between maternal hemoglobin and cord blood hemoglobin of their new-born.